Elevating regional competitiveness: How tourism and ICT development shape Indonesian provinces - Priambodo, Aji (Journal of Economics Research and Policy Studies, 2025)
This study examines the influence of tourism development and Information and Communication Technology (ICT) on regional competitiveness across Indonesian provinces. Using cross-sectional data from all provinces in 2022, the research employs multiple regression analysis with comprehensive classical assumption testing to assess these relationships. Data was sourced from three national institutions: the Regional Competitiveness Index from BRIN, tourism development data from the Ministry of Tourism and Creative Economy, and ICT development data from Central Bureau of Statistics. The analysis reveals significant positive relationships between both predictors and regional competitiveness, with tourism development emerging as the stronger predictor. The findings demonstrate that provinces investing in tourism development and ICT infrastructure gain substantial competitive advantages. These results provide important implications for policymakers, suggesting that an integrated approach incorporating both tourism and ICT development initiatives might yield optimal results for enhancing regional competitiveness. The study contributes to the understanding of regional development dynamics in developing economies, particularly in the Indonesian context, offering valuable insights for policy formulation and strategic planning in regional development.